Vawt Helix Turbine Design For Microhybrid Plants - Budi Artono; Yuli Prasetyo; Basuki Winarno; Dimas Nur Prakoso; Afifah Al Hayu Nugraheni (JURAL RISET RUMPUN ILMU TEKNIK, 2024)
Conventional power plants that exist today can cause environmental damage, such as air pollution and the erosion of fossil reserves. Therefore, humans continue to innovate to develop environmentally friendly power plants. One of them is the combined wind turbine and solar cell technology to create a more effective solution called a Hybrid power plant. This research proposes a VAWT Helix Turbine Design for Microhybrid Power Plant. The design is according to the wind speed and solar radiation for the Madiun city area. BMKG data shows that the average wind speed is 3 m/s to 7 m/s. Meanwhile, the sun's heat is on average 25°C to 36°C. The wind turbine uses 3 blades of helix type and the solar cell used is Monocrystalline. The design was designed using the AutoCAD program and simulated using Qblade software. The blades are made using 3D Printing Polylactic Acid (PLA) and then printed using a 3D Printer. Simulation results using Qblade show the average value when the wind speed is 3 m/s produces an average power within 11.4 Watt. When the wind speed is 4 m/s, the average power is 33.7 Watt. When the wind speed of 5 m/s produces an average power of 80.2 watts.